Workshop Basic Trauma & Cardiac Life Support (BT&CLS) terhadap pengetahuan dokter kecil pelajar SMA di Kota Bengkulu - Hidayat, Yance; Sofais, Danur Azissah Roesliana; Hermiati, Dilfera; Pebriani, Emi; Susanti, Meri Epriana (Holistik Jurnal Kesehatan, 2024)
Background: Indonesia is one of the countries that faces a double nutritional problem (double burden). Nutritional problems are an indicator that leads to non-communicable diseases that begin with obesity, especially at a young age. The problem of obesity among teenagers has increased quite significantly with prevalence findings reaching 34%. In other words, teenagers are a group of people who are at risk of developing diseases such as high blood pressure, heart attacks, and so on. Another problem that must be faced is the limited number of health workers. To overcome this, the government created a small doctor program to deal with health problems in schools.Purpose: To utilize a demonstration model involving pediatricians to increase knowledge in basic life support (BT) and cardiac life support (CLS).Method: Experimental study to analyze the effects of each treatment using two experimental concepts, namely small doctors in public and private high schools. Participants were divided into two groups, namely pre and post-test. This study took participants from high school students who had duties as junior doctors in high school and did not have skills in BT&CLS practice. The total number of schools taken was 60 schools, consisting of 30 private and 30 state high schools.Results: The demonstration model was more effective in small private school doctors. This means that this concept can be easily applied in private schools. The 95% Confidence Interval (CI) for public high schools is -12.3 to 2.24 and for private high schools is -15.64 to 2.77.Conclusion: Little doctors in private schools are more skilled than little doctors in public schools. However, overall using demonstration techniques in minor doctor training can increase students' BT&BLS knowledge.Suggestion: Public schools should provide more training to minor doctors to increase the life expectancy of patients in schools. This can help and save the patient's life. Keywords: Basic Life Support (BT); Cardiac Life Support (CLS); Little Doctor; Workshop. Pendahuluan: Indonesia merupakan salah satu negara yang menghadapi masalah gizi ganda (double burden). Masalah gizi merupakan indikator yang mengarah pada penyakit tidak menular yang diawali dengan obesitas, terutama pada usia muda. Masalah obesitas di kalangan remaja mengalami peningkatan yang cukup signifikan dengan temuan prevalensi mencapai 34% dengan kata lain, remaja merupakan kelompok masyarakat yang memiliki risiko terkena penyakit seperti tekanan darah tinggi, serangan jantung, dan sebagainya. Masalah lain yang harus dihadapi adalah terbatasnya tenaga kesehatan. Dalam mengatasinya, pemerintah membuat program dokter kecil untuk menangani masalah kesehatan di sekolah.Tujuan: Untuk memanfaatkan model demonstrasi yang melibatkan dokter kecil untuk meningkatkan pengetahuan dalam basic life support (BT) dan cardiac life support (CLS).Metode: Studi eksperimen untuk menganalisis efek dari setiap perlakuan menggunakan dua konsep eksperimen yaitu dokter kecil di SMA negeri dengan swasta. Partisipan dibagi menjadi dua kelompok, yaitu pra dan post-test. Penelitian ini mengambil partisipan dari siswa sekolah menengah atas yang memiliki tugas sebagai dokter junior di sekolah menengah atas dan tidak memiliki keterampilan dalam praktek BT&CLS. Total sekolah yang diambil adalah 60 sekolah, terdiri atas 30 SMA swasta dan 30 negeri.Hasil: Model demonstrasi lebih efektif pada dokter kecil sekolah swasta. Artinya, konsep ini dapat dengan mudah diterapkan di sekolah swasta. Confidence Interval (CI) 95% pada SMA Negeri adalah -12.3 sampai 2.24 dan pada SMA Swasta adalah -15.64 sampai 2.77.Simpulan: Dokter kecil di sekolah swasta lebih terampil daripada dokter kecil di sekolah negeri. Namun secara keseluruhan dengan menggunakan teknik demonstrasi dalam pelatihan dokter kecil dapat meningkatkan pengetahuan BT&BLS para siswa.Saran: Sekolah negeri harus memberikan lebih banyak pelatihan kepada dokter kecil untuk meningkatkan harapan hidup pasien di sekolah. Hal ini dapat membantu dan menyelamatkan nyawa pasien. Kata kunci: Basic Life Support (BT); Cardiac Life Support (CLS); Dokter Kecil; Workshop.